Iron biofortification interventions to improve iron status and functional outcomes - Finkelstein, Julia L.; Fothergill, Amy; Hackl, Laura S.; Haas, Jere D.; Mehta, Saurabh (Proceedings of the Nutrition Society, 2019)
This analysis was conducted to evaluate the evidence of the efficacy of iron biofortification interventions on iron status and functional outcomes. Iron deficiency is a major public health problem worldwide, with a disproportionate impact on women and young children, particularly those living in resource-limited settings. Biofortification, or the enhancing of micronutrient content in staple crops, is a promising and sustainable agriculture-based approach to improve nutritional status. Previous randomised efficacy trials and meta-analyses have demonstrated that iron-biofortification interventions improved iron biomarkers; however, no systematic reviews to date have examined the efficacy of biofortification interventions on health outcomes. We conducted a systematic review of the efficacy of iron-biofortified staple crops on iron status and functional outcomes: cognitive function (e.g. attention, memory) and physical performance. Five studies from three randomised efficacy trials (i.e. rice, pearl millet, beans) conducted in the Philippines, India and Rwanda were identified for inclusion in this review. Iron status (Hb, serum ferritin, soluble transferrin receptor, total body iron, α-1-acid glycoprotein) was measured at baseline and endline in each trial; two studies reported cognitive outcomes, and no studies reported other functional outcomes. Meta-analyses were conducted using DerSimonian and Laird random-effects methods. Iron-biofortified crop interventions significantly improved cognitive performance in attention and memory domains, compared with conventional crops. There were no significant effects on categorical outcomes such as iron deficiency or anaemia. Further studies are needed to determine the efficacy of iron-biofortified staple crops on human health, including additional functional outcomes and other high-risk populations.